African Film Festivals and Transnational Flows of Living Cultural Heritage - Petty, Sheila; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
(3z(BSure to become a key reference for anyone working on African film festivals, this volume offers a refreshingly pluri-centric perspective on the ways African stories travel across many continents and communities that constitute today's African film worlds.(3y $1 (BDr. Rachel Johnson, University of Leeds, United Kingdom (3z(BThis volume is an essential festival knowledge forum. Through a diverse set of case studies, the book offers highly engaging Indigenous, postcolonial, and diasporic perspectives, emphasizing the social impact, cultural exchange, and meaningful collaboration of and through Africa-themed film festivals.(3y $1 (BProf. Dr. Skadi Loist, Film University Babelsberg KONRAD WOLF, Germany (3z(BThis edited collection brings together a wide range of scholars and critics and provides a nuanced overview of the role played by international film festivals in shaping our understanding of African cinemas across the globe and the circuits through which African films circulate. A much-needed intervention in festival studies.(3y $1 (BDr. Antoine Damiens, York University, Canada This open access book investigates how flows of knowledge that arise from the African continent travel and are transformed through new contexts of presentation and engagement in new locations. Through case studies on Africa-themed film festivals in Africa, Europe and the Americas, the book explores potential methods of catalyzing a (3z(Btransnational flow(3y (Bfrom inception to end that involves attention to process, rather than studying festivals as static cultural products with discrete and isolated categories of programming, presentation, documentation, and networking. The chapters probe how festivals interact with place and location and create journeys of discovery in translating and contextualizing films for specific populations and audiences. The book also focuses on how dialogue is created in a festival-knowledge forum that respects the living nature of cultural heritage as it is received from its original context, presented during film festivals, and passed on to future generations for safeguarding. Sheila Petty is a Fellow of the Royal Society of Canada and Professor Emerita of Film Studies at the University of Regina, Canada. She has written extensively on cultural heritage in sub-Saharan African, North African and Amazigh cinemas. Her most recent book is Habiba Djahnine: Memory Bearer (2025).s
Chapter 1: Introduction: African Film Festivals and Transnational Flows of Living Cultural Heritage -- Chapter 2: On FESPACO Mythology -- Chapter 3: Curating Africa in Contemporary Film Festivals in Senegal: An Analysis of the Constellation of Collaborations -- Chapter 4: Journeys of Discovery: The Case of the New York Forum of Amazigh Film (NYFAF) -- Chapter 5: Virtualization of the New York Forum of Amazigh Film (NYFAF) During and Post- COVID-19: the Scramble (3z(BTo Remain the Same(3y (B-- Chapter 6: From Africa to London to the World: Film Africa$1 (Bs Leading Role in the Circulation of African Cinemas -- Chapter 7: African Film Festivals: A Transnational Programming Intervention and Tales of the Accidental City as a Case Study -- Chapter 8: (3z(BAct in Your Location, think with the World(3y(B: Constructing Audience (3z(BAfterlives(3y (Bat Three North American-based African Film Festivals.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Motion pictures -- Africa; Ethnology -- Africa; Culture; Emigration and immigration; African Film and TV; African Culture; Diaspora Studies